A Phenology Analysis of Palm Oil (Elaeis Guineensis Jacq) Growth Using Satellite Imagery Approach (A Case Study in Darul Makmur Sub-District, Nagan Raya Regency, Aceh) - Ijal Wandi; Sugianto Sugianto; Syakur Syakur (Rona Teknik Pertanian, 2022)
Abstract. Vegetation index values derived from the  Landsat-8 OLI images have been used widely to assess plant growth, especially in oil palm plantations. This study intends to estimate growth rates and establish the phenology of oil palm growth based on spectral reflection patterns. This study employed multitemporal Landsat-8 OLI images from 2013, 2014, 2017, 2020, and 2021 to visually interpret satellite imagery based on spatial and digital detection of object attributes. The phenology of oil palm growth is grouped into the Seed-0 Phase (0-1 Years), Seed Phase (1-3 Years), Young Phase (4-8 years), Teenage Phase (9-14 years), Mature Phase (15-20 years) and Old Phase ( 20 years). The results of the digital analysis of Landsat 8 OLI show that the spectral reflection pattern has almost the same shape at the same wavelength and varies in each phase of oil palm growth. The average NDVI vegetation index value shows a green peak in the teenage phase (0.908). The results of a simple linear regression averaging the NDVI vegetation index value with the average age data of each oil palm growth phase from the TBM-0 phase (0-1 year) to the old phase ( 20 years) yields a moderate relationship for the transformation of the vegetation index NDVI. The transformation of the NDVI vegetation index produces an R² with a value of 0.483 that the regression results formed above the adolescent phase (9-13 years) do not form a pattern